2010
DOI: 10.1186/1471-2148-10-205
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic diversity and fitness in multiple environments

Abstract: BackgroundWhen a large number of alleles are lost from a population, increases in individual homozygosity may reduce individual fitness through inbreeding depression. Modest losses of allelic diversity may also negatively impact long-term population viability by reducing the capacity of populations to adapt to altered environments. However, it is not clear how much genetic diversity within populations may be lost before populations are put at significant risk. Development of tools to evaluate this relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(177 citation statements)
references
References 52 publications
5
156
0
1
Order By: Relevance
“…This prediction has been supported in meta-analyses of data from animal and plant species (r¼0.45 (Reed and Frankham, 2003); rB0.3 (Leimu et al, 2006); r¼0.40, 0.49 (Markert et al, 2010)). By contrast, little relationship is expected between individual multilocus genetic diversity for near-neutral loci and reproductive fitness within populations, unless there is heterozygote advantage, inbreeding or population structure.…”
Section: Correlations Of Genetic Diversity With Population Size and Fmentioning
confidence: 61%
“…This prediction has been supported in meta-analyses of data from animal and plant species (r¼0.45 (Reed and Frankham, 2003); rB0.3 (Leimu et al, 2006); r¼0.40, 0.49 (Markert et al, 2010)). By contrast, little relationship is expected between individual multilocus genetic diversity for near-neutral loci and reproductive fitness within populations, unless there is heterozygote advantage, inbreeding or population structure.…”
Section: Correlations Of Genetic Diversity With Population Size and Fmentioning
confidence: 61%
“…In general, we found that salt-pond populations had a reduced effective population size as compared with natural populations. Lower genetic diversity has been observed as a factor compromising reproductive fitness in affected populations, increasing the risk of local extinction (Markert et al, 2010). More migrants were observed from salt ponds towards natural mangroves than vice versa.…”
Section: Genetic Diversitymentioning
confidence: 98%
“…For instance, the animal model [80] is now commonly used in the wild to estimate additive genetic variation, a critical component of the evolutionary potential of a trait. To our knowledge, no examples of the application of the animal model to ER yet exist; however, several authors have highlighted its potential [81][82][83]. High throughput genomic techniques with large sets of microsatellites loci and/or high-density SNP data provide helpful tools to achieve this objective [80].…”
Section: Future Directionmentioning
confidence: 99%